Analysis of Threats to the Physical Protection of Nuclear Facilities and Sites (UNWE Yearbook, 2020)
The modern trends in threats to international security, such as the nuclear arms race, terrorist threats through improvised explosive devices with radioactive materials, cyber-threats against hi-tech production and operating security systems, the 2011 earthquake with a 9.0 magnitude on the Richter scale which caused a tsunami, which in turn led to the Fukushima nuclear disaster, have drawn attention to the various dimensions and degrees of the physical vulnerability of nuclear sites and facilities.